Exploring risk, antecedents and human costs of living with a retained surgical item: A narrative synthesis of Australian case law 1981–2018 - Sonya Osborne; Tina Cockburn; Juliet Davis (Journal of Perioperative Nursing)
Objective(s): This study aimed to critically examine the circumstances contributing to, and the human costs arising from, the retention of surgical items through the lens of Australian case law.